Molecular symmetry and group theory - Carter, Robert L., 1944- (New York : J. Wiley, 1998)
In a friendly, easy-to-understand style, this new book invites the reader to discover by example the power of symmetry arguments for understanding theoretical problems in chemistry. The author shows the evolution of ideas and demonstrates the centrality of symmetry and group theory to a complete understanding of the theory of structure and bonding.
Plus, the book offers explicit demonstrations of the most effective techniques for applying group theory to chemical problems, including the tabular method of reducing representations and the use of group-subgroup relationships for dealing with infinite-order groups.
Ch. 1. Fundamental Concepts -- Ch. 2. Representations of Groups -- Ch. 3. Techniques and Relationships for Chemical Applications -- Ch. 4. Symmetry and Chemical Bonding -- Ch. 5. Equations for Wave Functions -- Ch. 6. Vibrational Spectroscopy -- Ch. 7. Transition Metal Complexes -- App. A. Point Group Character Tables -- App. B. Correlation Tables -- App. C. Normal Modes of Some Common Structures -- App. D. Tanabe and Sugano Diagrams.
Includes bibliographical references and index.
Keywords: Molecular theory; Symmetry (Physics); Group theory